STRUCTURAL POSITION MUTATION OF DISTRICT HEAD IN BIREUEN REGENCY - Rahmat Novissa; Aiyub; Maryam; Anismar; Nurhafni (RADJA PUBLIKA, 2025)
The Structural Position Mutation System for Sub-district Heads within the Bireuen Regency Government is not based on educational background and competence in its implementation. Unfortunately, there has been a neglect of Law Number 23 of 2014 concerning Regional Government. This study aims to describe the structural job mutation system of sub-district heads in the Bireuen Regency Government using three bases, namely the Merit System, Seniority System and Spoil System, and to analyze the inhibiting factors for structural job mutations of sub-district heads in Bireuen Regency including budget limitations, lack of human resources who master technical knowledge of government and bureaucratic culture. Qualitative methods with a descriptive approach have been used in this study. Researchers used observation, interviews, and documentation to answer two research objectives. The results of this study found that the implementation of the Merit System foundation has not been fully optimal, the Seniority System runs by prioritizing work period and work experience but not for age, the Spoil System can still provide gaps for politicization. The obstacles to its implementation are budget limitations, lack of human resources who master technical knowledge of government and bureaucratic culture. This study suggests that the Bireuen Regency government optimizes the performance assessment team in making mutation decisions using the Merit System, Seniority System and Spoil System foundations and optimizes the budget for the competence of prospective sub-district heads.